The Relationship Between Students Perceptions of Biology Teacher Competence and Students Learning Independence, Motivation, and Creativity in North Toraja Regency, South Sulawesi - Marrandan, Barnabas Pera; Junda, Muhammad; Ali, Alimuddin (Jurnal Pijar Mipa, 2025)
This study examines the relationship between students' perceptions of biology teacher competence with their learning independence, motivation, and creativity in North Toraja Regency. A quantitative approach with a correlational design was used. This study aims to determine the nature of the relationship between the perception of biology teacher competence with learning independence, learning creativity, and learning motivation, as well as the relationship between learning independence, creativity, and learning motivation of class XI IPA (Group F) students of State Senior High Schools in North Toraja Regency in the 2024/2025 academic year. Data collection was carried out through a questionnaire covering perceptions of teacher competence, learning independence, creativity, and motivation. Descriptive and inferential statistical analyses were carried out, including Pearson correlation tests and regression analyses. The results showed a significant positive correlation between perceptions of teacher competence with learning independence (r = 0.680), creativity (r = 0.766), and motivation (r = 0.849), with a p value of 0.000. These findings indicate that positive perceptions of teacher competence contribute to improving student learning outcomes.